265 PROGNOSTIC ROLE OF VITAMIN D DEFICIENCY IN STEMI PATIENTS UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION. (15th December 2022) - Verdoia, Monica; Gioscia, Rocco; Rolla, Roberta; Rognoni, Andrea; De Luca, Giuseppe
Abstract: Background and Aims: The pandemic proportion of vitamin D deficiency has raised particular concerns on its association with mortality and cardiovascular disease (CVD). However, the independent and causative role of hypovitaminosis D in CVD is still debated. Few data have been reported, so far, among STEMI patients undergoing primary percutaneous coronary intervention (pPCI), that was therefore the aim of the present study. Methods: A consecutive cohort of patients admitted for STEMI treated with pPCI were included. The levels of 25(OH)D were assessed at admission by chemiluminescence immunoassay kit LIAISON® Vitamin D assay (Diasorin Inc). Hypovitaminosis D was defined for 25(OH)D < 10 ng/ml. The primary study endpoint was net adverse cardiovascular events (a composite of death, recurrent MI and target vessel revascularization) at the longest available follow-up. Secondary endpoints were overall mortality, major bleedings or the individual components of the primary endpoint. Results: We included 136 patients divided according to tertiles values of 25(OH)D (< 12.98 ng/ml, n=44; 12.98-22.1 ng/ml, n=41; ≥ 22.1 ng/ml, n=51). The prevalence of renal failure (p=0.047) and coronary calcifications inversely related with vitamin D. Lower vitamin D levels were associated with "no reflow" (10.3% vs 6.7% vs 0%, p=0.04), with increased use of adenosine. At a mean follow-up of 305± 217 days (mean + SD), the primary endpoint (NACE) was slightly increased in patients with lower vitamin D values (adjusted HR [95% CI] = 3.07 [0.85-11.1], p = 0.09). Similar results were observed for ischemic events (MACE: adjusted HR [95% CI] = 2.78 [0.68-11.48], p = 0.16). However, when considering separately patients with severe hypovitaminosis D (<10 ng/ml), we found a significant increase in the risk of NACE and MACE (adjusted HR [95% CI] = 5.17 [1.42-18.8], p = 0.01 and HR = 4.75 [1.14-19.7], p = 0.03, respectively). Conclusion: The present study shows that among patients with STEMI undergoing pPCI, extremely low levels of vitamin D are independently associated with impaired outcomes. Future dedicated studies will shed light on the prognostic implications of hypovitaminosis D in these patients and the potential therapeutic perspectives.